The Development of Positive Father Scale: A Tool for Enhancing Family Dynamics - Eryilmaz, Ali; Uzun, Abdullah Ensar; Basal, Ahmet (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
The study aims to develop the Positive Father Scale, a tool for assessing positive father traits from a child's perspective. The stages of the cross-sectional research design involved interviewing individuals, developing a 24-item scale with four distinct sub-dimensions (behavioral closeness, autonomy support, conscientiousness, extraversion), testing the scale, and conducting factor, validity, and reliability analyses on two sample groups. The scale exhibited high consistency in all sub-dimensions and overall score, confirming its reliability and validity. This validated scale, designed to measure positive father traits, highlights characteristics of effective fathering, identifies areas for growth, and aids research in psychology, sociology, and family science. Future studies could utilize the Positive Father Scale across diverse cultural backgrounds and age demographics for long-term validation, and its adoption could pave the way for similar scales addressing other family roles, enriching our holistic understanding of family dynamics.
Keywords: family dynamics; positive father; scale development; scale validation; PERSONALITY-TRAITS; AUTONOMY-SUPPORT; INVOLVEMENT; HEALTH; CHILDREN; PARENTS; ADOLESCENTS; CHILDHOOD; INTIMACY; COLLEGE; Family Studies